2018
DOI: 10.1155/2018/3207973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allicin against Ischemia/Hypoxia‐Induced H9c2 Myoblast Apoptosis via eNOS/NO Pathway‐Mediated Antioxidant Activity

Abstract: Allicin (2-propene-1-sulfinothioic acid S-2-propenyl ester, diallyl thiosulfinate) is the main biologically active ingredient in garlic. The present study investigated the protective effect of allicin against cardiomyocyte apoptosis that was induced by ischemia in vitro and the potential molecular mechanisms that were involved in this antiapoptotic effect. The results indicated that allicin increased H9c2 cell activity and attenuated the rate of apoptosis that was induced by ischemia/hypoxia. Intracellular cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Nrf2 is a redox‐sensitive transcription factor that plays a pivotal role in cellular antioxidant defense. Nrf2 trans‐activation promotes the up‐regulation of antioxidant genes responsible for the expression of antioxidant enzymes 30 . This brings to mind that the effects of garlic on TAC may occur through increasing the intracellular antioxidants such as glutathione, uric acid, bilirubin, and by stimulating the expression of antioxidant enzymes 26,31 …”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a redox‐sensitive transcription factor that plays a pivotal role in cellular antioxidant defense. Nrf2 trans‐activation promotes the up‐regulation of antioxidant genes responsible for the expression of antioxidant enzymes 30 . This brings to mind that the effects of garlic on TAC may occur through increasing the intracellular antioxidants such as glutathione, uric acid, bilirubin, and by stimulating the expression of antioxidant enzymes 26,31 …”
Section: Discussionmentioning
confidence: 99%
“…Garlic (Allium sativum), a spice belongs to the Alliacae family, and its preparations have been widely recognized as agents for prevention and treatment of CVDs like atherosclerosis, hyperlipidemia, thrombosis, and hypertension [13]. Recent molecular studies have also demonstrated that active ingredients like s-allyl-cysteine sulfoxide (alliin) [14], diallyl trisulfide (DATS) [15], Allicin (2-propene-1-sulfinothioic acid S-2-propenyl ester, diallyl thiosulfinate) [16,17] of garlic protect cardiac tissue through down regulating the expression of some CVD causing apoptotic genes.…”
Section: Introductionmentioning
confidence: 99%
“…Allicin increased SOD and NO release activity, decreased MDA levels, significantly increased eNOS, Nrf2, and HO-1 protein expression and showed protective effect via antioxidant activity mediated by eNOS/NO pathway [25]. Another study found that allicin remarkably attenuated diabetes-induced decrease of NO production and eNOS expression, with a concomitant improvement in endothelial-dependent relaxation.…”
Section: Discussionmentioning
confidence: 99%